Model Pemberdayaan dan Kemandirian Ekonomi Di Pondok Pesantren Mamba’us Sholihin Gresik - Abdul Basit; Tika Widiastuti (Universitas Airlangga, 2019)
The purpose of this study was to compile a model of empowerment and a form of economic independence conducted at Mamba'us Sholihin Gresik Islamic Boarding School. The research method used is a descriptive qualitative approach with a case study method. Data collection was carried out by interviewing boarding school leaders, koppontren leaders, and leaders of pesantren social institutions, santri, surrounding communities, observation, and documentation. Secondary data collection came from journals, text books, boarding schools and literature. The results of this study are Islamic Boarding School Mamba'us Sholihin using a Muslim model in empowering santri through practice, training and becoming employees in the business units owned by Islamic boarding. Whereas in the empowerment of the surrounding community it is carried out through Islamic boarding social institutions, namely in the form of basic food assistance, routine studies, Ramadhan guidance, free medical assistance, and assistance in the event of a natural disaster. The manifestation of Islamic boarding’s economic independence is being able to meet the operational needs of Islamic boarding from the profit of the business units owned by the Islamic boarding.Keywords: Islamic Boarding School, Empowerment, Economic IndependenceREFERENCESAl-Quran Terjemahan. 2015. Departemen Agama RI. Bandung: CV DarusSunnah.Afifuddin dan Beni Ahmad Saebani. 2009. Metodologi Penelitian Kualitatif. Bandung: Pustaka Setia. Anas. 2012. “K.H. Mufid Mas’ud dan Aktivitas Dakwahnya di Dusun Candi Sardonoharjo Ngaglik Sleman”. Skripsi Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta. Tidak dipublikasikan.Basit, Abdul. 2009. “Program Pemberdayaan Ekonomi Pada Pondok Pesantren As-Salafiyah Desa Cicantayan Cisaat Sukabumi”. Skripsi FakultasDakwah dan Komunikasi Universitas Islam Negeri Syarif Hidayatullah. Jakarta: Repository UIN Jakarta. Dhofier, Zamakhsyari. 2005. Tradisi Pesantren: Studi Pandangan Hidup Kyai dan Visinya mengenai masa depan Indonesia. LP3ES: Jakarta.Dhofier, Zamakhsyari. 2011. Tradisi Pesantren. LP3ES: Jakarta.Emzir. 2012. Metodologi Penelitian Pendidikan Kuantitatif dan Kualitatif. Bandung: Rajagrafindo Persada. Halim, A. dkk. 2005. Manajemen Pesantren. Yogyakarta: Pustaka Pesantren.Madjid, Noer Cholis. 1997 Bilik-Bilik Pesantren: Sebuah potret perjalanan.Jakarta:Paramadina. Mahmud dan Khusnurdillo. 2005. Model-model pembelajaran di Pesantren. Jakarta:Diva Pustaka. Masrun, dkk. (1986). Studi Mengenai Kemandirian pada Penduduk di Tiga Suku Bangsa (Jawa, Batak, Bugis). Laporan Penelitian. Yogyakarta: PPKLH Universitas Gajah Mada.Mastuhu.1994. Dinamika Sistem Pendidikan Pesantren. Jakarta: INIS.Moleong, Lexy J. 2017. Metodologi Penelititan Kualitatif. Bandung: Remaja Rosda KaryaMoleong, Lexy J. 2010. Metodologi Penelititan Kualitatif. Bandung: Remaja Rosda Karya.Moleong, L. J. (1999). Metodologi penelitian. Bandung: PT. Remaja Rosda Karya.Muhtarom. 2005. Reproduksi Ulama’ di Era Globalisasi;Resistensi Tradisional Islam. Yogyakarta: Pustaka Pelajar. Muttaqin, R. 2011. Kemandirian dan Pemberdayaan Ekonomi Berbasis Pesantren. Jurnal Ekonomi Syariah Indonesia. Vol. 1(2): 65-94.Noor, dkk. 2006. Zakat dan Peran Negara. Jakarta: Forum Zakat Al-Utsaimin.Prijono. 1996. Pemberdayaan: Konsep, Kebijakan, dan Implementasi. Jakarta:CSIS. Qomar, Mujamil. 2006. Pesantren Dari Transformasi Metodologi Menuju DemokrasiQomar, Mujamil. 2008. Pesantren Dari Transformasi Metodologi Menuju DemokrasiRahmat, Ginanjar. 2014. Pemberdayaan Masyarakat Sebagai Bagian Dari Pembangunan Ekonomi Lokal. Skripsi. Departemen Ilmu Kesejahteraan Sosial, Universitas Indonesia Depok Jakarta.Rosyidi, S. (2006). Pengantar Teori Ekonomi:Pendekatan Kepada Teori Ekonomi Mikro dan Makro. Raja GrafindoPersada, Jakarta.Sanrego dan Taufik. 2016. Fiqih Tamkin (Fiqih Pemberdayaan). Jakarta: QisthiPress.Sugiyono. 2012.Metode Penelitian Bisnis. Bandung : AlfabetaSutrisno, Edi. 2009. Manajemen Sumber Daya Manusia Edisi Pertama. Jakarta: Kencana Prenada Media Grup. Yin, Robert K. 2015. Studi Kasus :Desain dan Metode. Jakarta: Raja Grafindo Persada.Yin, Robert K. 2010. Qualitative Research From Start to Finish. Jakarta: Raja Grafindo Persada. Yin, Robert K. 2008. Case Study Research: Design and Method (Applied Social Research Methods). Illinois: Sage Publications Inc. Yin, Robert K. 2014. Studi Kasus Desain & Metode. Jakarta: Rajawali Pers. Ziemek, Manfred. 1986. Pesantren dalam Perubahan Sosial. Jakarta: P3M Jakarta.(www.pondoktremas.com 19 April 2018 pukul 13.22 wib). (www.tafsircahcepu., diakses pada 18 September 2018 pukul 18.09). (www.republika.co.id/berita/ekonomi/syariahekonomi/17/12/25/p1i2oo382-bmt ugt-sidogiri-pasuruan-catat-pertumbuhan-positif dikutip pada 18 agustus 2018 pukul 11.20). (http://mamba’ussholihin.net/ dikutip pada 23 September 2018 pukul 09.40). (www.kemenag.go.id)(Mahdi Hadawi Tehrani, Maktab wa Nizhâm Iqtishâdi Islâm, hal. 83, Nainawa, Tahun 1383 S dikutip.